2020
DOI: 10.2147/idr.s286293
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bacterial Profiles and Antimicrobial Susceptibility Pattern of Isolates from Inanimate Hospital Environments at Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia</p>

Abstract: Introduction Microbial contamination of the hospital environment plays an important role in the spread of healthcare-associated infections (HCAIs). This study was conducted to determine bacterial contamination, bacterial profiles, and antimicrobial susceptibility pattern of bacterial isolates from environmental surfaces and medical equipment. Methods A cross-sectional study was conducted at Tikur Anbessa Specialized Hospital (TASH) from June to September 2018. A total o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
5
10
1
Order By: Relevance
“…In our study findings, contamination by Gram-positive bacteria was higher than that by Gram-negative bacteria. Similar findings are reported by other studies [ 19 , 20 ]. In contrast to our findings, a study from India reported higher contamination rates with Gram-negative bacterial isolates [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study findings, contamination by Gram-positive bacteria was higher than that by Gram-negative bacteria. Similar findings are reported by other studies [ 19 , 20 ]. In contrast to our findings, a study from India reported higher contamination rates with Gram-negative bacterial isolates [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…The overall bacterial contamination rate in ICU was 64.7% (152/235) which is higher than that in findings of other studies [ 18 , 19 ]. Some of the studies have reported higher percentage of bacterial contamination than our findings [ 20 , 21 ]. This reflects that bacterial contamination rates vary from hospital to hospital within and outside the country.…”
Section: Discussioncontrasting
confidence: 68%
“…pneumoniae displayed the highest resistance to two antibiotics, such as ciprofloxacin and tetracycline and this profile is comparable to the results of a prior study done in Hawassa, Ethiopia [ 31 ]. Besides, susceptibility profiles exhibited by isolates against trimethoprim-sulfamethoxazole, gentamicin, and amoxicillin-clavulanate were relatively similar to the results of an earlier work done in Addis Ababa, Ethiopia [ 37 ].…”
Section: Discussionsupporting
confidence: 81%
“…High-touch surfaces in the hospital are potential sources of nosocomial infections, which increases the risk of contamination among susceptible hosts [ 36 , 37 ]. In this study, the overall bacterial contaminations of high touch surfaces, leftover drugs, and 80% ethanol was 26.6%, which is lower than a study carried out at Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia (86%) [ 38 ]. This difference might be due to differences in diagnostic techniques and infection control policies.…”
Section: Discussionmentioning
confidence: 58%